2021
DOI: 10.1038/s41598-021-99414-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gamma irradiation on filtering facepiece respirators and SARS-CoV-2 detection

Abstract: To cope with the shortage of filtering facepiece respirators (FFRs) during the coronavirus (COVID-19) pandemic, healthcare institutions were forced to reuse FFRs after applying different decontamination methods including gamma-irradiation (GIR). The aim of this study was to evaluate the effect of GIR on the filtration efficiency (FE) of FFRs and on SARS-CoV-2 detection. The FE of 2 FFRs types (KN95 and N95-3 M masks) was assessed at different particle sizes (0.3–5 µm) following GIR (0–15 kGy) delivered at eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“… 8 10 Specifically, many methods of decontamination or sterilization have been previously reported, 10 , 11 including the use of γ and electron beam irradiation. 12 , 13 Additionally, Menon et al demonstrated that post-functionalization of PP masks can result in effective sterilization through the use of zinc porphyrin photosensitizers for enhancing the ability of the masks to protect against influenza pathogens. 14 Alternatively, masks can be collected and recycled through several processing steps, such as granulation and pelletization.…”
Section: Introductionmentioning
confidence: 99%
“… 8 10 Specifically, many methods of decontamination or sterilization have been previously reported, 10 , 11 including the use of γ and electron beam irradiation. 12 , 13 Additionally, Menon et al demonstrated that post-functionalization of PP masks can result in effective sterilization through the use of zinc porphyrin photosensitizers for enhancing the ability of the masks to protect against influenza pathogens. 14 Alternatively, masks can be collected and recycled through several processing steps, such as granulation and pelletization.…”
Section: Introductionmentioning
confidence: 99%
“…59 The reported data in Table 5 suggest that the tested mask has limited protection against aerosols after ionizing radiation sterilization, which is consistent with previous studies. 9,20,21,24,39…”
Section: Resultsmentioning
confidence: 99%
“…In the absence of a durable inhomogeneous electric field, the respirator’s filtration properties are reduced, which is observed in ionizing radiation sterilization. 9,20,21,24,39,61 The gamma irradiation produced significant bipolar ions (positive and negative ions) in the surrounding environment and in the respirator fiber material (electrons and/or holes). These ions attracted, trapped, de-trapped, and recombined in the PP fiber structure and modified their surface charge density.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations